Applying Family Communication Patterns to Patient-provider Communication: Examining Perceptions of Patient Involvement, Satisfaction, and Medical Adherence. Issue 2 (1st February 2020) - Rauscher, Emily A.; Hesse, Colin; Campbell-Salome, Gemme
Abstract : This study investigates patient perceptions of patient-provider communication and family communication patterns theory (FCPT). Using FCPT, the study predicts that family communicative environment relates to patient perceptions of patient involvement in care as well as patient satisfaction and medical adherence. Further, this study tests new measures of conformity orientation (warm and cold conformity) to investigate the multi-faceted nature of the variable. The results show significant relationships between FCPT and patient perceptions and outcomes. Specifically, warm conformity was the strongest and most reliable predictor of patient perceptions and outcomes across the three FCPT variables tested in the model. Additionally, results show differences between how warm and cold conformity predict patient perception and outcome variables. Finally, tests of the interaction between conversation orientation and both types of conformity indicate relationships between interaction variables and patient involvement in care, but not satisfaction or adherence. Practical implications and future research ideas are also discussed.